Comparative Outcome of Oral and Subcutaneous Methotrexate Therapy in Children with Juvenile Idiopathic Arthritis - Miah, Mamun; Hoque, Kazi Zahidul; Sultana, Akhand Tanzih; Alam, Md Zahangir (Ibrahim Cardiac Medical Journal, 2017)
Background & objective: Juvenile idiopathic arthritis (JIA) is the most disabling illness in children. There are number of disease modifying antirheumatic drugs (DMRDS). Methotrexate (MTX) is one of them and for the last two decades has become the cornerstone for the treatment of JIA, because of its efficacy and safety profile. However, debate is still continuing regarding its route of administration (orally or parenteraly) to have wider efficacy and safety. The present study was conducted to compare the outcome of oral and subcutaneous MTX in the treatment of JIA. Materials & Methods: This comparative clinical trial was conducted in Dhaka Shishu Hospital & Bangladesh Institute of Child Health, over a period of 3 years between January 2013 to December 2015. The study initially included 72 children; of them 22 dropped out or did not comply with treatment protocol and hence were excluded from final analysis. Of the remaining children 25 were in Oral and 25 in subcutaneous group. Primary outcome was defined as the percentage of patients reaching ACR Pedi 30 improvement criteria after 6 months of treatment. The ACR Pedi 30 was reached if there was an improvement of ≥30% in at least 3 of 6 core variables, with no worsening of >1 of the remaining variables by ≥30%. Results: The study demonstrated that children with JIA responded well to MTX treatment irrespective of their route of administration, as was evidenced by the achievement of ACR Pedi 30 criteria by majority of the children after 6 months of treatment. However, in terms of core set of variables, subcutaneous route worked better and faster than the oral route. The mean numbers of active joints in the Oral group dropped from 5 at baseline to nearly 2 and < 2 at 3 and 6 months respectively, which in the Subcutaneous groups dropped from 6 at baseline to 2 and < 1 at 3 and 6 months respectively. The average numbers of joints with limited range of motion at baseline in the Oral and Subcutaneous groups were 3 and > 3 which decreased to 1 and < 1 respectively at month 6. Likewise patient/parents’ global assessment of overall wellbeing improved earlier in Subcutaneous group than that in the Oral group (p < 0.001). Physician’s global assessment of disease activity also responded better in the subcutaneous group compared to that in the Oral group (p < 0.001). The C-HAQ disability index in the Oral group reduced insidiously from 1.3 at baseline to 0.4 at 6 months; in contrast the same parameter steeply decreased from 1.5 at baseline to 0.0 at 6 months indicating that Children Health Assessment Questionnaire responded rapidly to Subcutaneous MTX. The ESR in Oral group decreased from 79 at baseline to < 40 at month 3 and to close to 30 mm at month 6, which in the Subcutaneous group decreased from over 70 at baseline to < 30 and < 20 at month 3 and 6 respectively indicating that the decrease being much faster in the latter group. Conclusion: The study concluded that children with JIA responded well to MTX treatment irrespective of their route of administration, as was evidenced by the achievement of ACR Pedi 30 criteria by majority of the children after 6 months of treatment. However, considering the response in terms of core set of variables, it appears that subcutaneous route worked better and faster than the oral route did. Ibrahim Card Med J 2015; 5 (1&2): 27-34